Human capital and the agrarian structure in transition: Micro evidence from Romania - Marian Rizov (Economic and Industrial Democracy, 2005)
This paper examines determinants of the agrarian structure in transition economies with an emphasis on the role of rural households' human capital. Farm restructuring has resulted in a broad range of farm types, such as co-operatives, partnerships, individual farms and combinations of them. In our theoretical model the fact that household resources are allocated into different organization modes is attributed to the utility maximization strategy of heterogeneous agents deriving income from uncertain sources in the face of absent or imperfect factor markets. Empirical results from a multinomial logit model estimated with data from two-year nation-wide survey of Romanian rural households support the hypothesis that the current agrarian structure is primarily determined by both the human capital characteristics of and economic risks faced by the households.
Keywords: D10; J20; P20; R20; 330; human capital; rural households; farming; economic transition